Inflammatory linear verrucous epidermal nevus. - Caprio, F. (European Journal of Pediatric Dermatology, 2018)
The inflammatory linear verrucous epidermal nevus (ILVEN) is characterized by early onset, often at birth and by intense itching (1). These characteristics serve to differentiate it from other blaschko-linear dermatitis such as psoriasis, lichen planus, lichen striatus and blaschkitis of the adult. The last condition is the one that most resembles ILVEN. We described in the past a case of unius lateris left epidermal nevus present since birth that at the age of 49 was complicated on the same line by an eczematous pruritic dermatitis that we labeled as blaschkitis (2). Another less known aspect of ILVEN is its variability over time. It can start as a warty epidermal nevus and then become inflammatory in some areas or totally, it tends to worsen over time but it may also undergo stable or transient regression of the inflammatory component.